Medical, psychological and social features in a large cohort of adults with Prader–Willi syndrome: experience from a dedicated centre in France. (20th June 2014) - Laurier, V.; Lapeyrade, A.; Copet, P.; Demeer, G.; Silvie, M.; Bieth, E.; Coupaye, M.; Poitou, C.; Lorenzini, F.; Labrousse, F.; Molinas, C.; Tauber, M.; et al.
Abstract Background Prader–Willi syndrome (PWS) is a developmental genetic disorder characterised by a variable expression of medical, cognitive and behavioural symptoms. In adulthood, the prevalence and severity of these symptoms determine the quality of life of the affected persons. Because of their rare disease condition, data on health and social problems in adults with PWS are scarce. In this research, we present medical, psychological and social features of a large cohort of adults admitted to a specialised PWS centre in France and analyse the differences according to genotype, gender and age. Methods Data from154 patients (68 men/86 women), with a median age of 27 years (range 16–54), were collected during their stay in our centre. Clinical histories were completed using information from parents or main caregivers, and the same medical team performed the diagnosis of different clinical conditions. Statistical analyses were performed to determine the influence of factors such as genotype, age or gender. Results Paternal deletion genotype was the most frequent (65%) at all ages. Most patients had mild or moderate intellectual disability (87%). Only 30% had studied beyond primary school and 70% were in some special educational or working programme. Most of them lived in the family home (57%). The most prevalent somatic comorbidities were scoliosis (78%), respiratory problems (75%), dermatological lesions (50%), hyperlipidaemia (35%), hypothyroidism (26%), Type 2 diabetes mellitus (25%) and lymph oedema (22%). Some form of psychotropic treatment was prescribed in 58% of subjects, and sex hormones in 43%. Patients with deletion had a higher body mass index (44 vs. 38.9 kg/m2) and displayed higher frequency of sleep apnoeas. Non‐deletion patients received insulin treatment (19% vs. 4%) and antipsychotic treatment (54.8% vs. 32.7%) more frequently. No difference was observed in the prevalence of Type 2 diabetes between the two genotype groups. Patients >27 years of age had a higher rate of comorbidities (Type 2 diabetes, hypertension, respiratory problems and lymph oedema). Gender differences were minor. Conclusions Adult patients with PWS showed high prevalence of comorbid health problems that need to be monitored for early treatment. Some of them are influenced by genotype and age. Another salient problem concerns the lack of adapted structures for better social integration. Further data about the real life and health conditions of adults with PWS are necessary to further our knowledge of the natural history of the disease and to design appropriate care strategies.